Proximate Analysis of Talinum triangulare (Water Leaf) Leaves and its Softening Principle - Aja, P.M.; Okaka, A.N.C.; Ibiam, U.A.; Uraku, A.J.; Onu, P.N. (Pakistan Journal of Nutrition, 2010)
The proximate analysis of Talinum triangulare was carried out in both wet and dry conditions respectively. The results revealed the presence of carbohydrates (10.87±3.99 mg/g and 12.38±2.76 mg/g), steroids (106.61±2.53 mg/100mg and 11.37±1.19 mg/100g), protein (3.52±0.32% and 18.75±2.72%), oil content (3.52% and 1.44%), b-Carotene (114.5±1.49 mg/g and 40.02±0.50 mg/g) and crude fibre (12.00% and 8.50%) in dry and wet samples respectively. The wet sample was assayed for pectinases at various temperatures. This revealed the presence of pectinases with specific activities of 38.64 units/kg protein, 55.44 units/kg protein, 61.14 units/kg protein and 62.09 units/kg protein at 35, 55, 75 and 95oC respectively. These results indicate that the leaves contain an appreciable amount of nutrients and should be included in our meal for a balanced diet. The high amount of pectinases detected lends credence to the traditional use of water leaf as a softener of other vegetables species and a possible industrial application.